High-risk human papillomavirus infection prevalence in non-malignant tonsillar tissue: A single-center cross-sectional study: Human papillomavirus infection prevalence - Bayram , Gül; Simsek , Tugce; Hazir , Selin; Ozen , Fatma Zeynep; Erdogan , Mehmet Mustafa; Seyhan , Sinan; Kazaz , Hasan; Tezcan , Erkan (Journal of Surgery and Medicine, 2023)
Background/Aim: The prevalence of human papillomavirus (HPV) in non-malignant tonsils can vary according to geographical location, age group, and risk factors. Some studies have found a relatively low prevalence of HPV, while other studies have found higher rates in non-malignant tonsils. The presence of HPV in non-malignant tonsils may be associated with precursor lesions that have the potential to develop into cancer. The aim of the current study was to detect the prevalence of HPV and p16 (one of the HPV types) in non-malignant tonsils and determine the existence of HPV in tonsil tissue using molecular and histological techniques. Methods: One hundred-three samples from non-malignant tonsils and one sample from squamous cell carcinoma of the tonsils were analyzed for the prevalence of HPV using molecular and histological methods. Real-time polymerase chain reaction (qPCR) was performed to detect HPV in the tissue samples. Results: HPV was not found in any tissue specimens based on histopathological and p16 immunohistochemical evaluations. HPV was not detected in all tissue samples using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). Conclusions: In our study of one hundred and four patients, HPV and p16 were not genetically detected in the tonsils that underwent surgery for reasons other than cancer. Hence, more comprehensive studies can contribute to evaluating the relationship between benign tonsil tissue and HPV infection, potentially leading to improved diagnostic and preventative measures.